Association of thiol disulfide homeostasis with slow coronary flow. (3rd July 2016) - Kundi, Harun; Gok, Murat; Cetin, Mustafa; Kiziltunç, Emrullah; Topcuoglu, Canan; Neşelioğlu, Salim; Erel, Ozcan; Ulusoy, Feridun Vasfi
Abstract: Objective The aim of this study was to investigate the role of thiol disulfide homeostasis in the presence of slow coronary flow.Material and methods In this cross-sectional study, a total of 110 patients who admitted to our hospital between March 2014 and December 2015 were included in the study. There were 65 patients in the slow coronary flow, and 45 patients in the normal flow groups.Results We found significant differences between slow coronary flow and the normal flow groups for thiol disulfide homeostasis, and the results of our study indicated that hsCRP, and thiol disulfide ratio were independently associated with slow coronary flow.Conclusion Our study showed that thiol disulfide homeostasis was significantly and independently related to the presence of slow coronary flow.